Holistic or analytic rubrics? Grading information literacy instruction. Issue 2 (3rd April 2019) - Badia, Giovanna
Abstract: Studies about the assessment of information literacy instruction have reported the use of specific grading criteria, also known as rubrics, to evaluate students' responses. Rubrics can be divided into two general categories: (1) holistic, where one score is assigned for evaluating the successful completion of a task; and (2) analytic, where a grade is subdivided into discrete components needed to complete the task and each component is given its own score for achievement. This article will investigate which scoring method—employing holistic versus analytic rubrics—is the most effective for evaluating students' search strategies in terms of providing constructive feedback to students and informing the librarian's future teaching practices.